2018
DOI: 10.3390/polym10060586
|View full text |Cite
|
Sign up to set email alerts
|

High Permittivity Nanocomposites Embedded with Ag/TiO2 Core–Shell Nanoparticles Modified by Phosphonic Acid

Abstract: In this paper, nanocomposites that contain core-shell Ag/TiO 2 particles as the filler and polytetrafluoroethylene (PTFE) as the matrix were investigated. Two surfactants, namely octyl phosphonic acid (OPA) and pentafluorobenzyl phosphonic acid (PFBPA), were applied to modify Ag/TiO 2 fillers for uniform dispersion in the matrix. Fourier transform infrared spectroscopy analysis of bonds between the TiO 2 shells and the phosphonic modifiers sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Two main strategies have been developed by researchers to enhance the dielectric permittivity [5,6,7,8,9,10,11,12]. One is incorporating ceramic fillers with intrinsically high dielectric constants (e.g., BaTiO 3 , Ba x Sr 1-x TiO 3 , CaCu 3 Ti 4 O 12 ) [13,14,15,16,17,18,19,20] into the polymer matrix; the other strategy is employing conductive fillers, including metals (e.g., Ag, Ni, Al) [21,22,23,24,25], carbon materials (e.g., carbon nanotubes, graphene) [26,27,28,29,30,31,32], semiconductors (e.g., ZnO) [33], and conductive polymers (e.g., polyaniline (PANI)) [34,35,36,37]. With ceramic/polymer composites, the merits of high ε r from ceramic fillers and high breakdown strength from polymers are combined.…”
Section: Introductionmentioning
confidence: 99%
“…Two main strategies have been developed by researchers to enhance the dielectric permittivity [5,6,7,8,9,10,11,12]. One is incorporating ceramic fillers with intrinsically high dielectric constants (e.g., BaTiO 3 , Ba x Sr 1-x TiO 3 , CaCu 3 Ti 4 O 12 ) [13,14,15,16,17,18,19,20] into the polymer matrix; the other strategy is employing conductive fillers, including metals (e.g., Ag, Ni, Al) [21,22,23,24,25], carbon materials (e.g., carbon nanotubes, graphene) [26,27,28,29,30,31,32], semiconductors (e.g., ZnO) [33], and conductive polymers (e.g., polyaniline (PANI)) [34,35,36,37]. With ceramic/polymer composites, the merits of high ε r from ceramic fillers and high breakdown strength from polymers are combined.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, how to effectively realize the uniform dispersion of nanoparticles in polymer substrate is still a difficult problem to be solved. To address this problem, researchers have also adopted surface modification and in situ generation of nanoparticles [ [199] , [200] , [201] , [202] , [203] , [204] ], but most of the methods involved are complicated and introduce other redundant substances, potentially harming the clinical use, and it is still difficult to achieve uniform dispersion in the real sense. Therefore, more effective and environmentally friendly methods that can realize uniform dispersion of metal nanoparticles remain to be studied.…”
Section: Antibacterial Coatingsmentioning
confidence: 99%
“…Thus, the results showed that the nanocomposites by PFBPA exhibits higher permittivity than the OPA because of its uniform dispersion stability of inorganic fillers into the PTFE polymer matrix and results increase the interfacial polarization effect. Therefore, nanocomposites could be used as better promising materials for applications of embedded devices and high frequency fields in electronics [87].…”
Section: Figure 2 Thermal Conductivity Of (A) Al 2 O 3 -Ag Nps-epoxy Composites As a Function Of Ag Contents (B) Variation Of Thermal Conmentioning
confidence: 99%